Óleo essencial de capim-limão (Cymbopogon citratus stapf.) apresenta ação inseticida e sedativa e causa inibição de acetilcolinesterase em Drosophila Melanogaster Meigen - Silva Thaís Posser, Luan da Rosa (2025)
Essential oils (EOs) represent promising alternatives to synthetic pesticides, offering bioactive properties with less environmental impact. This study investigated the biological effects of Cymbopogon citratus (lemongrass) essential oil and isolated components on Drosophila melanogaster, evaluating their insecticidal, sedative, and anticholinesterase properties in vivo and in vitro. The components used, geraniol, myrcene, and linalool, were chosen based on a chromatographic study of the oil. First, a dose curve was made, where adult flies were exposed to EO at doses of 0.25 μL, 0.5 μL, and 1 μL for 1 hour by fumigation and then transferred to tubes without the presence of oil to verify effective mortality, where they remained for 3 hours. The rate of active flies decreased significantly after 50 minutes at 0.25 μL, 40 minutes at 0.5 μL, and 30 minutes at 1 μL, with a recovery of 100% at 0.25 μL, 60% at 0.5 μL, and 30% at 1 μL, the latter being set as the working dose. Then, at a dose of 1 μL, the flies were exposed for 25 minutes with a recovery time of 2 hours, where a drop in the number of active flies to 5% could be observed after 25 minutes, with a return of 76% after 2 hours of cessation of exposure. Acetylcholinesterase enzyme activity was measured in vitro, showing a significant reduction compared to the control, and in vivo, where a significant reduction in enzyme activity was observed after 2 hours of recovery compared to the control. The components geraniol, myrcene, and linalool were tested individually and in co-exposures where, in the first scenario, only linalool showed a significant sedative effect after 1 hour with 64% recovery after 2 hours, and in the second scenario, where flies coexposed to geraniol and linalool and to myrcene and linalool showed total sedation after 1 hour with recovery of 5% and 37%, respectively, those coexposed to myrcene and geraniol showed only 20% sedation, with no recovery. The results of this study indicate that EO has a dose- and time-dependent effect, partially inhibits the action of acetylcholinesterase, and that a component that may be related to the sedative effect is linalool, in synergy with other components. Thus, EO is a promising candidate for a natural pesticide against fruit flies, which brings the study in line with the UN Sustainable Development Goals 3 and 12, which aim to reduce the use of synthetic pesticides and, with this, the diseases caused by them.